Unsteady temperature fields of evaporating water droplets exposed to conductive, convective and radiative heating. (25th February 2018) - Kuznetsov, G.V.; Piskunov, M.V.; Volkov, R.S.; Strizhak, P.A.
Graphical abstract: Highlights: Uniform field is generated by radiant heating 30 times faster than by convective one. Uniform field is formed by radiant heating 200 times faster than by conductive one. Radiant heating has the greatest impact due to radiation absorption in the droplet. PLIF confirms importance of droplet temperature field unsteadiness and non-uniformity. Droplet heating time to boiling temperature may take up to 60–75% of droplet lifetime. Abstract: In this paper, we present the rates and typical durations of high-temperature heating and evaporation of water droplets determined for the dominating conductive, convective or radiative energy supply. We developed three setups for heating a water droplet: on a substrate (conduction), in a muffle furnace (radiation), and in a heated airflow (convection). The heating temperature is up to 1000 °C to correspond high-temperature technologies, namely thermal cleaning of fluids, polydisperse fire extinguishing with low water consumption, etc. With the help using of a high-speed video recording system, we determine the water droplet lifetimes (the times of their complete evaporation). Using Planar Laser Induced Fluorescence, we establish the quantitative differences between the water droplet heating rates (heating time to lifetime ratios) on the three setups. Maximum temperatures are determined that the water droplets reach when exposed to different heating mechanisms. Furthermore, we obtain the criterial dependences to connect the main attributes of temperature field generation of an evaporating water droplet with the heating conditions. Finally, we identify possible implications of the research findings and ways to further improve the newly developed experimental approach.